Friction Stir Welding of Al-B4C Composite Fabricated by Accumulative Roll Bonding: Evaluation of Microstructure and Mechanical Behavior - BOZKURT, YAHYA (SPRINGER, 2018)
In this investigation, friction stir welding (FSW) of Al-B4C composite fabricated by 10 cycles accumulative roll bonding was conducted. In order to investigate the influences of pin geometry on microstructure and mechanical properties, four different pin geometries (cylindrical, square, triangular and hexagonal) were selected. It was found that FSW parameters had a major effect on the fragmentation and distribution of reinforcement particles in stir zone. When the tool travel speed was increased, the distribution of B4C particles was become gradually uniform in the aluminum matrix. The effect of tool rotational speed on the peak temperature was determined to be greater than the tool travel speed. The attained data of tensile properties and microhardness tests showed that the tool travel speed had bilateral effect on the tensile strength. The maximum tensile joint efficiency was obtained as 238% for FSWed of Al-2%B4C composite to annealed base Al sheet.
Keywords: accumulative roll bonding; friction stir welding; peak temperature; pin geometry; tensile strength; tool rotational speed; TOOL PIN PROFILE; SURFACE NANO-COMPOSITE; ROTATIONAL SPEED; PROCESSING ZONE; AL-ALLOY; OPTIMIZATION; PARAMETERS; JOINTS